1957
DOI: 10.4039/ent89371-8
|View full text |Cite
|
Sign up to set email alerts
|

A Virus Disease and Introduced Parasites as Factors Controlling the European Spruce Sawfly, Diprion hercyniae (Htg.), in Central New Brunswick

Abstract: An outbreak of the European spruce sawfly, Diprion hercyniae (Htg.), was discovered in the Gaspé Peninsula in 1930. By 1938, heavy infestations had developed west of the Gaspé Peninsula in Quebec, throughout New Brunswick and northern Maine, and in parts of Vermont and New Hampshire. Moderate to light infestations occurred through all other parts of the spruce forests of this region and extended from Nova Scotia, to the north shore of the St. Lawrence River, and west to Ontario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1959
1959
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 7 publications
0
38
0
1
Order By: Relevance
“…A large body of theoretical work now exists on the effects of disease on the dynamics of plant and animal populations (Anderson and May 1981;Anderson 1982;Begon et al 1992;Bowers et al 1993;Godfray 1995, 1996;Godfray and Briggs 1995) but experimental testing of the resulting hypotheses has tended to lag behind theory. Insect-pathogen systems have provided some of the very few data sets on long-term host-pathogen dynamics, which are necessary for the validation of the theoretical work (Bird and Elgee 1957;Hofmaster 1961;Fleming et al 1986). However, many of these data sets come from field populations, in which environmental factors, which may affect host dynamics (Myers 1988), cannot be separated from the effects caused by interactions between the host and pathogen alone.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of theoretical work now exists on the effects of disease on the dynamics of plant and animal populations (Anderson and May 1981;Anderson 1982;Begon et al 1992;Bowers et al 1993;Godfray 1995, 1996;Godfray and Briggs 1995) but experimental testing of the resulting hypotheses has tended to lag behind theory. Insect-pathogen systems have provided some of the very few data sets on long-term host-pathogen dynamics, which are necessary for the validation of the theoretical work (Bird and Elgee 1957;Hofmaster 1961;Fleming et al 1986). However, many of these data sets come from field populations, in which environmental factors, which may affect host dynamics (Myers 1988), cannot be separated from the effects caused by interactions between the host and pathogen alone.…”
Section: Introductionmentioning
confidence: 99%
“…By the end of the project, over 843 million individuals were released, with another 247 million released in the United States of America (Dowden 1962;McGugan and Coppel 1962). Despite this massive effort, classical biological control agents were not responsible for the eventual decline of the European spruce sawfly, but instead it was attributed to a nucleopolyhedralvirus, GhNPV (formerly Borrelinavirus hercyniae), brought in with agents during the 1930s (Bird and Elgee 1957). This virus spread quickly to wild European spruce sawfly populations causing significant mortality (Bird and Elgee 1957), and resulted in a shift in biological control work to mass-production of GhNPV (reviewed by van Frankenhuyzen et al 2015).…”
Section: The Early Era: 1882-1945mentioning
confidence: 99%
“…In recent years, the introduction and colonization of insect pathogens have been highly successful with the polyhedrosis viruses of certain saw- Viruses of the European spruce and pine sawflies, once they are intro duced artificially into a susceptible host population, spread (in one case over 500 feet in one year) and persist for many years (11,23,26,27). Steinhaus (194) have found that the soil in alfalfa fields contained polyhedrosis virus that is infectious for the alfalfa caterpillar.…”
Section: Methods Of Applicationmentioning
confidence: 98%
“…Bird & Elgee (27) have speculated that the recent continual increase of the European spruce sawfly without a subsequent rapid rise in polyhedrosis suggests for the first time an increase in the resistance of the sawfly to the disease. Martignoni (123) has observed that in a population of the larch bud moth the LD50 of a granulosis virus increased from 1954 to 1955.…”
Section: Methods Of Dispersalmentioning
confidence: 98%